2021
DOI: 10.7150/thno.60531
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated NMDAR-enhanced GABAergic transmission underlies autistic-like deficits in Htr3a knockout mice

Abstract: Mutations in serotonin pathway genes, especially the serotonergic receptor subunit gene HTR3A , are associated with autism. However, the association of HTR3A deficiency with autism and the underlying mechanisms remain unknown. Methods: The Htr3a knockout (KO) mice were generated using transcription activator-like effector nuclease technology. Various behavior tests, including social interaction, social approach task, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…S15D-F). Previous study on Htr3a knockout mice reported increased excitability of hippocampal Pv+ INs (35), the major type of inhibitory neurons innervating PNs (36,37). We, therefore, speculate that Htr3a+ INs J o u r n a l P r e -p r o o f may innervate Pv+ INs and de-repress its inhibition on PNs, which may explain the increased excitability of cortical PNs in Setdb1-Gad2-cKOs.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 66%
“…S15D-F). Previous study on Htr3a knockout mice reported increased excitability of hippocampal Pv+ INs (35), the major type of inhibitory neurons innervating PNs (36,37). We, therefore, speculate that Htr3a+ INs J o u r n a l P r e -p r o o f may innervate Pv+ INs and de-repress its inhibition on PNs, which may explain the increased excitability of cortical PNs in Setdb1-Gad2-cKOs.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 66%
“…Whole-cell patch-clamp recordings of CA1 neurons were obtained as previously described. 75 Mice were anesthetized deeply with diethyl ether and decapitated. The brain was quickly dissected out and placed in ice-cold dissection buffer (220 mM sucrose, 2.5 mM KCl, 1.3 mM CaCl 2 , 2.5 mM MgSO 4 , 1 mM NaH 2 PO 4 , 26 mM NaHCO 3 , and 10 mM glucose).…”
Section: Methodsmentioning
confidence: 99%
“…Although grooming was not the focus of this study, the authors do briefly mention that grooming was not affected by 2-methyl-5-HT exposure. More recently, Huang et al (2021) employed a Htr3a knockout mouse and measured RRB expression. Compared to the wild type, Htr3a KO mice displayed elevated self-grooming rates, suggesting that reduced 5-HT3A receptors development may lead to increased repetitive grooming behavior.…”
Section: -Ht3mentioning
confidence: 99%